THE IMPROVEMENT OF STUDENTS LEARNING OUTCOMES AND ACADEMIC SELF EFFICACY USES PROBLEM BASED LEARNING (PBL) MODEL OF THE X IA-4 GRADE IN SMA BATIK 1 SURAKARTA IN ACADEMIC YEAR 2013/2014 - -, Fitriana D U, Maridi, Bowo Sugiharto (Pendidikan Biologi, 2015)
The purposes of the research is to increase students learning outcomes and academic self  efficacy uses problem  based learning model of the X IA-4 grade in SMA Batik 1 Surakarta in academic year 2013/2014.This research is a Classroom Action Research  with 2 cycles of action. Each cycle consist of 4 phases those are planning, action, observation, and reflection. The subject of this research are students of X IA-4 grade in SMA Batik 1 Surakarta in academic year 2013/2014. The data of this research obtained through test, observation, documentation and interview. The data analyzing technique uses qualitative descriptive technique. The data validation technique uses triangulation methods.The result of this research shows that by classroom action  uses  Problem Based Learning model can increase students learning outcomes and academic self efficacy in learning Biology. This statement is based on the test, observation, documentation  and  interview  result. The percentage of average score each indicator which is gotten from the observation result of students skills in the first cycle is 70,24% and the second cycle is 79,03% (worked up 8,79%), the score percentage of each indicator which is gotten from the observation result of students attitudes in the first cycle is 70,00% and  the second cycle is 79,15% (worked up 9,15%). The percentage of average score  each  indicator which is gotten from observation result of students academic self efficacy in the first cycle is 68,90% and the second cycle is 76,40% (worked up 7,50%).Based on the result, the conclusion is that Problem Based Learning model can increase students learning outcomes and academic self efficacy of X IA-4 grade in SMA Batik 1 Surakarta academic year 2013/2014.   Keywords : Problem Based Learning Model, Academic Self Efficacy, Learning Outcomes